2017
DOI: 10.2136/sssaj2016.08.0269
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Legume Cover Crops Can Increase Non‐Growing Season Nitrous Oxide Emissions

Abstract: Abbreviations: FRC, fall rye with compost; FRF, fall rye with inorganic fertilizer; MDL, minimum detection limit; ORC, oilseed radish with compost; ORF, oilseed radish with inorganic fertilizer; NCC, no cover crop with compost; NCF, no cover crop with inorganic fertilizer; CON, nonamended soil with no cover crop; WEOC, water-extractable organic carbon. P ost-harvest seeding of cover crops reduces the risk of wind erosion and nutrient loss through leaching and runoff during the non-growing season, but how cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 60 publications
0
16
2
Order By: Relevance
“…While many reviewed CC effects on soil properties (Blanco-Canqui et al, 2015), C sequestration (Poeplau and Don, 2015;, soil biology (Vukicevich et al, 2016;Finney et al, 2017), and other topics, an overall synthesis of CC biomass production under different cropping systems, management systems, CC species, and climatic conditions across temperate regions worldwide is not available. Individual studies suggest that CC biomass production can be highly variable, even within the same region (Finney et al, 2016;Thomas et al, 2016Thomas et al, , 2017.…”
Section: Core Ideasmentioning
confidence: 99%
“…While many reviewed CC effects on soil properties (Blanco-Canqui et al, 2015), C sequestration (Poeplau and Don, 2015;, soil biology (Vukicevich et al, 2016;Finney et al, 2017), and other topics, an overall synthesis of CC biomass production under different cropping systems, management systems, CC species, and climatic conditions across temperate regions worldwide is not available. Individual studies suggest that CC biomass production can be highly variable, even within the same region (Finney et al, 2016;Thomas et al, 2016Thomas et al, , 2017.…”
Section: Core Ideasmentioning
confidence: 99%
“…Based on these amounts, nitrate-N concentration in the surface 30 cm in the early fall, mid-spring, early winter, early spring, mid-spring, and early summer were 9.09, 10.24, 6.76, 6.55, 0.91, and 10.66 mg NO 3 -N kg −1 , respectively. For some of the application dates, the NO 3 -N concentrations may have been low enough in the unfertilized treatments to increase the conversion of N 2 O to N 2 (Blackmer & Bremner, 1979;Thomas et al, 2017).…”
Section: Soil Inorganic N Concentrationsmentioning
confidence: 99%
“…Studies investigating gas fluxes under different CC termination dates are very few. In many studies, CCs are terminated early with low biomass production (<1 Mg ha −1 ), which may reduce gas fluxes (Negassa et al, 2015; Thomas et al, 2017). For example, Negassa et al (2015) showed that CO 2 and N 2 O fluxes were not affected when CC biomass yield was below 0.5 Mg ha −1 .…”
mentioning
confidence: 99%
“…For example, Negassa et al (2015) showed that CO 2 and N 2 O fluxes were not affected when CC biomass yield was below 0.5 Mg ha −1 . Similarly, CO 2, N 2 O, and CH 4 fluxes were unaffected when CC biomass yield was 0.5 to 1.11 Mg ha −1 (Guardia et al, 2016; Thomas et al, 2017). However, CO 2 fluxes, but not N 2 O and CH 4 fluxes, were affected by larger quantities of CC biomass yield, such as 4.11 Mg ha −1 (Sanz‐Cobena et al, 2014).…”
mentioning
confidence: 99%